Tafsir Di Zaman Rasulullah SAW Dan Karakteristiknya - Mohamad Ghozi (Pena Islam Jurnal Pendidikan Agama Islam, 2022)
Understanding al-Quran is not the same as understanding text. Understanding text is sufficient for the untellectual capacity of the mind. Jowever, understanding alquran is not enough with the power of mind but must be supported by other sciences such as ulumul quran, then know about the asbab nuzul, nash mansukh, Makky and Madani and other discussion. Beside ulumul quran there re things that cannot underestimated, namaely the history of interpretation of the quran. The writing in this article is related to the history of riting interpretation of alquran in order to get a complete and correct understanding of alquran.